The Experience of Mature Malaysian Postgraduates in a university in England: Learning Challenges - Faizahani Ab Rahman (Proceedings of The ICECRS, 2017)
To date, the increasing number of research on international students in higher institutions in the United Kingdom has generally focused on the experiences of mainly the undergraduates coming from various countries. Research that explores the experiences of international postgraduates has recently concentrated on Chinese students as they comprise a high percentage of international students’ population in England. This paper, in contrast, draws on the experiences of a group of mature Malaysian postgraduates in a university in the south-west England and focuses on their learning experiences. The qualitative feasibility study of 16 Malaysian postgraduates suggests that their learning challenges are exclusively to them being mature students such as challenges in managing time and roles, international students in terms of language barriers and racial discrimination and postgraduates, such as meeting the expectations of their supervisors and other parties and meeting the demands of research work and ethics. This leads to suggestions on the types of support that mature Malaysian postgraduates studying abroad would need to help with the completion of their PhDs.